Posttraumatic Stress Disorder, Parenting, and Marital Adjustment among a Civilian Population - Hershkowitz, Michal; Dekel, Rachel; Fridkin, Shimon; Freedman, Sara (Frontiers in Psychology, 2017)
While psychopathology in general is linked to poorer marital and parental satisfaction, there is a paucity of data regarding these interactions in parents with PTSD. The current study addresses this issue among a civilian population. Two hundred trauma-exposed parents, mean age of 37.2, 62% mothers, were assessed using self-report questionnaires, for background variables, PTSD symptoms using the PDS, depression symptoms (BDI), marital satisfaction (DAS-7), parenting behavior (APQ-9) and parenting satisfaction (Parenting Satisfaction Questionnaire). We hypothesized that positive parenting behavior and parenting satisfaction would be negatively correlated with PTSD symptom levels, and that this relationship would be mediated by marital satisfaction; the independent effects of depression on marital and parenting functioning were also examined. Data was analyzed using structural equation modeling. Results indicated that PTSD was related to poorer parenting behavior (B= .089, p=.033), depression had a negative impact on parenting satisfaction (B= .983, p=.003) and marital satisfaction (B=-.672, p=.004), and marital satisfaction fully mediated the relationship between depression and parenting. The findings demonstrated that the effects of PTSD can cast a pall not only over the individual but over the entire family. Interventions are needed to address these issues.